2020
DOI: 10.1164/rccm.201903-0505oc
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Accuracy of a Deep Learning Method to Risk Stratify Indeterminate Pulmonary Nodules

Abstract: Rationale: The management of indeterminate pulmonary nodules (IPNs) remains challenging, resulting in invasive procedures and delays in diagnosis and treatment. Strategies to decrease the rate of unnecessary invasive procedures and optimize surveillance regimens are needed. Objectives: To develop and validate a deep learning method to improve the management of IPNs. Methods: A Lung Cancer Prediction Convolutional Neural Network model was trained using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
97
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 44 publications
(53 reference statements)
5
97
0
Order By: Relevance
“…Most studies did not state whether portions of data were missing or how missing data were handled. Lastly, some studies [39][40][41][42][43][44][45] did not externally validate findings with external datasets, missing a crucial step to evaluate the model's performance with completely independent datasets.…”
Section: Computer Vision For Lung Nodule Detection and Prediction Rismentioning
confidence: 99%
“…Most studies did not state whether portions of data were missing or how missing data were handled. Lastly, some studies [39][40][41][42][43][44][45] did not externally validate findings with external datasets, missing a crucial step to evaluate the model's performance with completely independent datasets.…”
Section: Computer Vision For Lung Nodule Detection and Prediction Rismentioning
confidence: 99%
“…This approach has shown promising results to discriminate benign from malignant lung nodules. 64,102,[146][147][148][149] However, these models have a tendency toward overfitting and will require extensive real-world validation to ensure their transportability to other settings. Furthermore, these "black box" algorithms lack obvious clinical interpretations that may limit widespread clinical adoption, though advancements in understanding and interpreting deep networks may help in this regard.…”
Section: Q What Are the Recent Advances In Machine Learning And Deepmentioning
confidence: 99%
“…150,151 Deep neural networks have produced impressive accuracy on traditional image classifications and object detection tasks. [147][148][149][150]152 To demonstrate that medical images can be automatically interpreted effectively to determine if a clinical action is indicated without requiring a human read of the images, the Google team recently showed that screening LDCT can be used to build an end-to-end approach to simulate the radiologist's workflow by performing both localization and lung cancer risk categorization tasks using the whole CT volume. 102 The deep learning algorithm equaled or out-performed radiologist readings.…”
Section: Q What Are the Recent Advances In Machine Learning And Deepmentioning
confidence: 99%
“…In this issue of the Journal , Massion and colleagues (pp. 241–249 ) report the development and external validation of a novel, computer-aided, deep learning–based radiomic model, the Lung Cancer Prediction Convolutional Neural Network (LCP-CNN), to distinguish benign nodules from malignant screen-detected and incidentally detected indeterminate pulmonary nodules ( 8 ).…”
mentioning
confidence: 99%
“…Massion and colleagues’ ( 8 ) LCP-CNN model represents another promising radiomic model for the classification of both screen-discovered and incidentally discovered pulmonary nodules. The reported AUCs are excellent at 0.92, 0.84, and 0.92 in the NLST (training set, screen-detected), Vanderbilt University, and Oxford University (validation sets, incidental) sets, respectively ( 8 ). The LCP-CNN model outperformed the clinical Mayo Clinic lung-nodule-malignancy probability model for both external validation sets ( 8 ).…”
mentioning
confidence: 99%